THE DEVELOPMENT OF LISTENING SKILL IN ENGLISH LANGUAGE - Xujamova, Mohinabonu Ma’rufjon qizi; Menlibayeva, Mereke Orazbayevna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article highlights some innovative strategies for improving listening skill of English Language of secondary level students. Effective Listening in English language, guiding the students towards effective oral communication, is the problem with all the ESL students at secondary level and as such it creates problem for English language teachers. The objective of the study was to help the English language teachers and students to overcome thisproblem by showing the results of application of innovative strategies for improving English language listening skill.